Possibilities and paradox : an introduction to modal and many-valued logic - Beall, J. C.; Van Fraassen, Bas C., 1941- (Oxford : Oxford University Press, 2003)
'Based on extensive classroom experience, Possibilities and Paradox goes beyond simply explaining how logic systems work - encouraging us to approach the systems in an informed and engaged way by giving new perspectives on the reasons and motivations which drive them. Beall and van Fraassen consider how we can tackle logic in practice, giving philosophical background in order to spark further discussion. Included are the motivations for non-classical logic in the Liar paradox, vagueness, and'paraconsistent' reasoning from inconsistent premises, as well as the more standard'possible world' semantics for modal and intuitionistic logic.'.
'The book opens up topics to debate, suitable for an intermediate course in logic. Each chapter contains innovative features that guide us through the subject: exercises to give students hands-on experience, examples to demonstrate the application of concepts, and lists of further reading.'--BOOK ACKET.
I. Preliminaries -- 1. Philosophical Motives -- 2. Set- Theoretic Tools -- 3. Languages and Logics -- 4. Tableaux -- II. Possibilities -- 5. Normal Modal Logics -- 6. Variations on a Theme -- III. Paradox -- 7. Around Truth and Falsity -- 8. Gaps, Gluts, and Liars -- 9. Heaps, Supertruth, and the Continuum -- IV. Metatheory -- 10. Further Tools -- 11. Logical Systems and Completeness -- 12. Meta-Theorems for Non-Classical Logics.
Includes bibliographical references : (pages 225-230) and index.
Keywords: Modality (Logic).; Many-valued logic